Positions 13 and 914 in Escherichia coli 16S ribosomal RNA are involved in the control of translational accuracy. - Pinard, R (1994)
Using a conditional expression system with the temperature-inducible lambda PL promoter, we previously showed that the single mutations 13U-->A and 914A-->U, and the double mutation 13U-->A and 914A-->U in Escherichia coli 16S ribosomal RNA impair the binding of streptomycin (Pinard et al., The FASEB Journal, 1993, 7, 173-176). In this study, we found that the two single mutations and the double mutation increase translational fidelity, reducing in vivo readthrough of nonsense codons and frameshifting, and decreasing in vitro misincorporation in a poly(U)-directed system. Using oligodeoxyribonucleotide probes which hybridize to the 530 loop and to the 1400 region of 16S rRNA, two regions involved in the control of tRNA binding to the A site, we observed that the mutations in rRNA increase the binding of the probe to the 530 loop but not to the 1400 region. We suggest that the mutations at positions 13 and 914 of 16S rRNA induce a conformational rearrangement in the 530 loop, which contributes to the increased accuracy of the ribosome.